Epigenetic patterns in a complete human genome - Gershman, Ariel; Sauria, Michael E G; Guitart, Xavi; Vollger, Mitchell R; Hook, Paul W; Hoyt, Savannah J; Jain, Miten; Shumate, Alaina; Razaghi, Roham; Koren, Sergey; Altemose, Nicolas; Caldas, Gina V; et al. (Science (American Association for the Advancement of Science), 2022)
The completion of a telomere-to-telomere human reference genome, T2T-CHM13, has resolved complex regions of the genome, including repetitive and homologous regions. Here, we present a high-resolution epigenetic study of previously unresolved sequences, representing entire acrocentric chromosome short arms, gene family expansions, and a diverse collection of repeat classes. This resource precisely maps CpG methylation (32.28 million CpGs), DNA accessibility, and short-read datasets (166,058 previously unresolved chromatin immunoprecipitation sequencing peaks) to provide evidence of activity across previously unidentified or corrected genes and reveals clinically relevant paralog-specific regulation. Probing CpG methylation across human centromeres from six diverse individuals generated an estimate of variability in kinetochore localization. This analysis provides a framework with which to investigate the most elusive regions of the human genome, granting insights into epigenetic regulation.